Nuts and Nut Products in Human Health and Nutrition - Rao, Venketeshwer; Rao, Leticia; Ahiduzzaman, Md; Aminul Islam, A. K. M. (IntechOpen, 2021)
Nuts, including peanuts, have always been an important part of the human diet. They are nutrient-dense food products containing health-friendly lipids, beneficial phytonutrients, and other essential vitamins and minerals. Basic, clinical, and epidemiological research is now being directed towards understanding the mechanisms by which nuts influence human health and developing dietary guidelines for their optimum consumption. Research is also being directed towards the issues of fungal contamination of nuts, associated risks to human health, and methods of minimizing such risks. This book addresses these topics in chapters written by international experts in the field.